Role of the oral microbiota in cancer evolution and progression. (7th July 2020) - Sun, Jiwei; Tang, Qingming; Yu, Shaoling; Xie, Mengru; Xie, Yanling; Chen, Guangjin; Chen, Lili
Abstract: Bacteria identified in the oral cavity are highly complicated. They include approximately 1000 species with a diverse variety of commensal microbes that play crucial roles in the health status of individuals. Epidemiological studies related to molecular pathology have revealed that there is a close relationship between oral microbiota and tumor occurrence. Oral microbiota has attracted considerable attention for its role in in‐situ or distant tumor progression. Anaerobic oral bacteria with potential pathogenic abilities, especially Fusobacterium nucleatum and Porphyromonas gingivalis, are well studied and have close relationships with various types of carcinomas. Some aerobic bacteria such as Parvimonas are also linked to tumorigenesis. Moreover, human papillomavirus, oral fungi, and parasites are closely associated with oropharyngeal carcinoma. Microbial dysbiosis, colonization, and translocation of oral microbiota are necessary for implementation of carcinogenic functions. Various underlying mechanisms of oral microbiota‐induced carcinogenesis have been reported including excessive inflammatory reaction, immunosuppression of host, promotion of malignant transformation, antiapoptotic activity, and secretion of carcinogens. In this review, we have systemically described the impact of oral microbial abnormalities on carcinogenesis and the future directions in this field for bringing in new ideas for effective prevention of tumors. Abstract : Oral microbiota has been playing an important role in the development of cancer throughout human body. Thus we try to summarize the current researches about this topic.